Layanan Belajar Anak Anak Berkebutuhan Khusus Di Gereja Serpong Tangerang - m kusuma wardhani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Pelita Harapan University as one of the Christian educational institutions, has a goal, one of which is to produce a community service program to build individuals and communities according to God's design. In line with this goal, the profile of Faculty of Education graduates is to become a significant member of the community by building a community based on grace, peace, hope and love. Therefore, Pelita Harapan University Faculty of Education students have a significant role in building society through community service programs. The Learning Services Program conducted does not only cover formal education such as schooling, but also in non-formal education such as tutoring. While the target is not only for normal children, but also for children with special needs. The purpose of this study is to see how the impact of the role of students through community service programs for children with special needs consisting of mild to moderate autism, down syndrome, and ADHD at Yayasan Edukasi dan Sosial in Tangerang . The method used is descriptive qualitative. Through evaluation, the role of students is seen especially in terms of helping children in fine motor development, helping to focus and follow the instructions given, and helping children interact with their peers. In addition, it also answers the needs of parents to perform devotion while their children are served by students who carry out the community service program.